Evaluation of clinical and functional outcome of total hip arthroplasty in avascular necrosis of head of femur in adults - Lingayat, M. B.; Baria, Karan; Muslim, Sufyan M.; Chavan, Santosh B.; Shaikh, Shanshah (International Journal of Research in Orthopaedics, 2023)
Background: Aim of the study was to evaluate clinical and functional outcome of bipolar hemiarthroplasty in avascular necrosis (AVN) of HIP in adults. Methods: Thirty patients of either sex between age group 20-80 years of age came for the treatment at government medical college and hospital Aurangabad. Between December 2020 to December 2022. Patients were followed every day till the discharge. Patients were discharged after they were mobilised with assistance of physiotherapist. Functional and clinical outcome was measured at 6, 12 and 24 weeks postoperatively according to Harris hip score (HHS). Results: the methods show significant improvement in HHS in patient undergoing total hip replacement. Conclusions: total hip replacement is a very good option for AVN of head of femur in all age groups.